1989 World Catalog of Centrosema Germplasm - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2016)
This catalog compiles and cross references the accessions in the world's major Centrosema collections at ClAT, ILCA, CSIRO. EMBRAPA-CENARGEN, and AREC Fort Pierce-University of Florida. It is a colIaborative effort by the curators of these collections under !he coordination of Dr. Ruiner Schultze•Kraft of CIAT. IBPGR is pleased to join with CIAT in the publication of this catalog.